From an open‐access fishery to a regulated aquaculture business: the case of the most important Latin American bay scallop (Argopecten purpuratus). (10th February 2018) - Kluger, Lotta C.; Taylor, Marc H.; Wolff, Matthias; Stotz, Wolfgang; Mendo, Jaime
Abstract: The South Pacific bay scallop Argopecten purpuratus represents a high‐value species harvested along the Peruvian and Chilean coastline for more than 60 years. Following the strong El Niño event of 1983/84, both countries experienced a boom in scallop fisheries, but catches dropped as soon as environmental conditions normalized. Aquaculture production began in Chile, which dominated the Latin American scallop market in the 1990s. Peruvian production remained small until the early 2000s, but has increased dramatically ever since, with a single location in northern Peru, Sechura Bay, contributing most (50%) to the Latin American scallop production. We review the historical trends of this species' production and analyse the ecological and socio‐economic factors that have favoured Sechura Bay's progress, and largely displaced Chilean production through dominance of the market. Advantageous environmental conditions in Sechura Bay (e.g. low water depths, higher temperatures, high natural seed supply) result in improved scallop growth and production, and the socio‐economic factors, causing lower operational costs than those of the Chilean production favoured this development. The bottom‐up initiation of aquaculture operations by small‐scale producers likely created a personal incentive for the long‐term sustainable use, which differs from the more industrialized aquaculture activities in Chile.